SHOWER BATH: AN EFFECTIVE STRATEGY TO PAIN RELIEF IN LABOR (Fiep Bulletin - online, 2013)
It is a therapeutic intervention type quantitative trial “before-after” used to evaluate the effectiveness of shower bath as a non-pharmacological strategy to minimize the labor-related pain in parturients during the active phase of labor. The study was conducted the Intensive Labor unit (UPH) of Januário Cicco Maternity School (MEJC), in the city of Natal, Northeast Region, Brazil. The study population was composed of parturients with a low-risk pregnancy when they were accepted for labor assistance. The sample comprised 100 women. To evaluate the intensity of pain a Visual Analogue Scale (VAS) was used. The data collection period was developed in 6 months, from September 2005 to February 2006. Observing the implementation of the non-pharmacological “shower bath” during a 8cm and 9cm size of cervical dilation, a significant difference was found (ñ=0,000) on two occasions in the active phase of labor, confirming the effectiveness of this strategy . Face the qualitative aspect of pain at two moments (8cm and 9cm) when compared at “before-after” of the isolated non-pharmacological (shower bath) implementation. Is conclusive that shower bath is an effective technique for pain relief and comfort of parturients at maximum acceleration and inclination of labor's active phase. The results of this study indicate the need for clinical research to evidence the use of these and other effective non-pharmacological strategies for labor pain relief, focusing on humanization assistance actions to parturients.
Keywords: Labor; Pain; Women Health.